An Unusual Presentation of Gastric Diverticulum – a Rare Form of Gastrointestinal Tract Diverticulum - Schuh, Gabriela Jungblut (Clinical and Biomedical Research, 2020)
In this report, we present two cases of gastric diverticulum (GD) documented by upper gastrointestinal contrast radiographic studies and computed tomography (CT). The first one, a 51-year-old woman, has a typical presentation, with the GD occurring in the posterior wall of the fundus (figure 1). The second one, a 72-year-old woman, has a sliding diaphragmatic hernia. In this patient, the gastric fundus, which also has a diverticulum, is herniated, being located inside the thorax (figure 2 and figure 3). Both patients discovered the presence of gastric diverticula incidentally during diagnostic testing for other reasons.